Modelling of low-energy/low-velocity impact on Nomex honeycomb sandwich structures with metallic skins - Castanie, Bruno; Bouvet, Christophe; Aminanda, Yulfian; Barrau, Jean-Jacques; Thevenet, Pascal (Elsevier, 2008)
In the aircraft industry, manufacturers have to decide quickly whether an impacted sandwich needs repairing or not. Certain computation tools exist at present but they are very time-consuming and they also fail to perfectly model the physical phenomena involved in an impact. In a previous publication, the authors demonstrated the possibility of representing the NomexTM honeycomb core by a grid of nonlinear springs and have pointed out both the structural behaviour of the honeycomb and the influence of core-skin boundary conditions. This discrete approach accurately predicts the static indentation on honeycomb core alone and the indentation on sandwich structure with metal skins supported on rigid flat support. In this study, the domain of validity of this approach is investigated. It is found that the approach is not valid for sharp projectiles on thin skins. In any case, the spring elements used to model the honeycomb cannot take into account the transverse shear that occurs in the core during the bending of a sandwich. To overcome this strong limitation, a multi-level approach is proposed in the present article. In this approach, the sandwich structure is modelled by Mindlin plate elements and the computed static contact law is implemented in a nonlinear spring located between the impactor and the structure. Thus, it is possible to predict the dynamic structural response in the case of low-velocity/low-energy impact on metal-skinned sandwich structures. A good correlation with dynamic experimental tests is achieved.